Radiofrequency Catheter Ablation of Atrial Tachycardias in Congenital Heart Disease: Results With Special Reference to Complexity of Underlying Anatomy. (December 2017) - Klehs, Sophia; Schneider, Heike E.; Backhoff, David; Paul, Thomas; Krause, Ulrich
Abstract : Background: Radiofrequency catheter ablation has become the treatment strategy of choice for atrial tachyarrhythmias in patients with congenital heart disease (CHD). We analyzed results of radiofrequency catheter ablation in a large cohort of patients with CHD with special reference to complexity of underlying anatomy. Methods and Results: One hundred and forty-four patients with CHD and atrial tachyarrhythmias undergoing radiofrequency catheter ablation were classified according to complexity of underlying CHD: simple CHD, n=18 (12%); moderate CHD, n=53 (37%); and complex CHD, n=73 (51%). Overall acute success was achieved in 81% of the patients. Acute success was lower for tachycardias involving the left atrium compared with right atrial tachycardias. Complexity of CHD was associated with longer procedure duration. Tachycardia recurrence was observed in 54% of the patients after a total follow-up of 7.4 years. 75% of all recurrences occurred within the first year. Recurrence of tachycardia was more likely in patients with complex surgical atrial anatomy (ie, Fontan palliation or atrial switch procedure). Major complications occurred in 4 patients and were related to vascular access. Conclusions: Acute procedural success of atrial tachycardia ablation in congenital heart patients was not influenced by complexity of CHD. Long-term outcome with regard to tachycardia recurrence was worse in patients with complex surgical atrial anatomy.